The Role of Social Capital in the Development of Fried Chicken Business - Ida Rosada; Farizah D Amran; Nurliani Nurliani; Rasmeidah Rasyid; Siti Hikmalia (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2023)
This study aims to describe the social capital owned by the owners, employees, and suppliers of raw materials for MSME fried chicken